The Efficacy of Herbal Medicines for Treatment of Hot Flash: A Systematic Review - L Kashani; F Khajuei Kermani; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2017)
Background: Hot flashing is the most common symptoms experienced by women around the menopause time. The most common therapy for relief of menopausal symptoms is Hormone Replacement Therapy (HRT), but it has side effects. So, many women are interested in herbal medicines because of fear of side effect of hormone therapy. Objective: The aim of this study was assess the effectiveness of different herbal medicine on the hot flash in menopausal women in clinical trial. Methods: The database of Medline, Scopus, and Web of Science were searched to investigate randomized controlled clinical trials on the efficacy of herbal medicines on hot flash from Feb 1994 to Feb 2017. Results: Fifty nine randomized controlled trials found according to the inclusion criteria. The results demonstrating that different herbal medicines such as Glycine max, Cimicifuga racemose, Vitex agnus-castus, Glycyrrhiza glabra, Trigonella foenum-graecum, Humulus lupulus, Valeriana officinalis, Linum usitatissimum, Salvia officinalis, Pimpinella anisum, Trifolium pretense, Hypericum perforatum and Ginkgo biloba can have role in reduction of the hot flashes. Conclusion: Our study show that many herbal medicines can reduce the frequency and number of hot Flash but it needs more future studies to find reliable result.